Предмет: Алгебра,
автор: NikitosMir
Помогите пожалуйста.
Log6(x+3)=1-log6 3
Приложения:
Ответы
Автор ответа:
1
ОДЗ
x > - 3
log6 (x + 3) = 1 - log6(3)
log6 (x + 3) = log6(6) - log6(3)
log6(x + 3) = log 6 (2)
x + 3 = 2
x = - 1
ОТВЕТ
x = - 1
x > - 3
log6 (x + 3) = 1 - log6(3)
log6 (x + 3) = log6(6) - log6(3)
log6(x + 3) = log 6 (2)
x + 3 = 2
x = - 1
ОТВЕТ
x = - 1
Похожие вопросы
Предмет: Химия,
автор: nagimullina1979
Предмет: Математика,
автор: Dark203
Предмет: Биология,
автор: lilseeko
Предмет: Математика,
автор: мир95
Предмет: Алгебра,
автор: NasyaVorobey1